Cyclization of Multi Components Reactions and (Preparation, Investigation, Thermal Curves) - Aljamali, Nagham Mahmood; Abd Allattif, Nour Abd Alrazzak; Abdalrahman, Sabreen Ali (American International Journal of Multidisciplinary Scientific Research, 2018)
Many  cyclic  compounds were  formatted  via  multi  components  reactions and cyclization  reaction  through  many  steps  with ( various   conditions , various  starting  materials , various  components ), in  first  step , aromatic amine derivative  were  reacted  with  ammonium thiocyanate  in cyclization  reaction   to  yield  2-aminobenzothiazole derivative , which  reacted  with  formaldehyde  and  benzaldehyde  as  a multi components   reaction ., then  the  resulting  compounds  cyclized  with ( semicarbazide , ortho-phenyl diamine , ortho-thiol aniline , ortho- amino phenol ). Investigation  of  compounds   carried out   through  many  techniques ( FT.IR , H.NMR , Mass ) – Spectra  , Thermal  studies